A Hierarchical (Macro)molecular Assembly Assisted by Donor–Acceptor Charge‐Transfer Interactions Exhibiting Room‐Temperature Ferroelectricity. (20th April 2022) - Mukherjee, Anurag; Barman, Shubhankar; Ghosh, Anupam; Datta, Ayan; Datta, Anuja; Ghosh, Suhrit
Abstract: This communication reveals co‐assembly of an electron‐deficient naphthalene‐diimide (NDI)‐appended polyurethane (P1) and electron‐rich pyrene (Py), forming an organogel with prominent room‐temperature ferroelectricity. In a non‐polar medium, intra‐chain hydrogen‐bonding among the urethane groups of P1 produces a folded structure with an array of the NDIs in the periphery, which intercalate Py by charge‐transfer (CT)‐interaction. Such CT‐complexation enables slow crystallization of the peripheral hydrocarbons, causing gelation with nanotubular morphology, in which the wall consists of the alternating NDI−Py stack. Such D‐A assembly exhibits ferroelectricity (saturation polarization P s ≈0.8 μC cm −2 and coercive field E c ≈8 kV cm −1 at 500 V and 10 Hz frequency) with Curie temperature ( T c ) of ≈350 K, which can be related to the disassembly of the CT‐complex. In the absence of Py, P1 forms spherical aggregates, showing dielectric behaviour. Abstract : Charge‐transfer interactions aid the formation of the tertiary structure of an aromatic acceptor‐appended polymer. The presence of an aromatic donor produces an organogel with nanotubular morphology, which exhibits room‐temperature ferroelectricity.